Transisi aliran gas-cair berlawanan arah ke searah pada saluran nearly horizontal dengan variasi bentuk penampang saluran. - Perpustakaan UGM, i-lib ([Yogyakarta] : Pusat Manajemen Pelayanan Kesehatan, Fak. Kedokteran UGM, 2001)
Effect of crossectional shape variations of the channel on the flooding phenomena in a nearly horizontal pipe has been performed through an experimental research. This work uses water and air with counter-current flow in two types of channel. Those channels are a circular channel with diameter 24 mm and a square channel with 21.5 mm height. The length of each channel is 150 cm with Bellmouth type for the inlet and outlet section. This research is conducted in room temperatures of 24Â°C- 30Â° C. This research shows that fluid thickness in square channel is thinner than in circular channel. It is imply that flooding phenomena occurs more easily in circular type than in square type.